Rekontekstualisasi Nilai-Nilai Pancasila dalam Pembinaan Karakter Siswa Melalui Morning Activity di SDN Cigabus - Nayla Maharani; Oki Suprianto; Firman Robiansyah (Publikasi Pendidikan, 2026)
This study aims to analyze the implementation of morning activities as a character building program for students and the process of recontextualizing Pancasila values for elementary school students at SDN Cigabus, Serang City. This study was conducted to gain an understanding of the integration of Pancasila values in routine morning activities and their reinterpretation in accordance with the social development, school culture, and digital reality of elementary school students. The study used a descriptive qualitative approach with a case study method carried out in the SDN Cigabus environment through observation, interviews, and documentation. Data analysis was carried out by referring to Thomas Lickona's character education theory which includes moral knowing, moral feeling, and moral action as well as the concept of recontextualizing Pancasila values. The results showed that morning activities at SDN Cigabus were carried out routinely through morning lines, greetings and shaking hands with teachers, joint prayers, reading short letters, flag ceremonies, Friday sermons, clean Fridays, and morning exercises, which functioned as a means of fostering religious character, discipline, responsibility, politeness, mutual cooperation, social care, and love for the homeland. The values of Pancasila are recontextualized by linking them to the real experiences of elementary school students, including social media ethics, responsible use of gadgets, cooperation, simple deliberation, and fair division of tasks, thus forming religious character, discipline, responsibility, social concern, and student participation in school life.